Pelatihan Pemanfaatan Aplikasi Google Drive dan Google Meet bagi Guru di SDN Kalianget X Sumenep - Tri Wahyuni C; Brigitta Septarini Rahmasari; Habanias Kurli; Abqari Safura; Tina Rosanti; Inika Sari (Jurnal Pengabdian UNDIKMA, 2022)
The aim of this community service activity is to provide training for teachers at SDN Kalianget Timur X Sumenep, regarding the use of google meet and also google drive. The methods used are online training, and online and offline mentoring. The isntruments are Questionnaire and Documents. The descriptive analysis is use to analyze the data. The results of this community service activity are 75% of teachers are able to operate google meet and also 65% of teachers have used the google drive application in file storage and 45% of teachers have tried using the google form application to make quizzes/tests.